Periodismo de viajes en la era digital: Cómo buscan la información las audiencias en España y en Rusia - Dra. Mariia LEKANT (Fonseca, Journal of Communication, 2023)
Travel journalism has undergone a transformation in the last decade with the advance of the Internet and the emergence of blogs dedicated to this subject, while the market for traditional magazines has contracted. At the same time, the media today must face new habits and demands from readers.